Investigating Prosecutor Policies Related To Completion Deadline Of Financial Losses Calculation Of The Corruption Case By Internal Government Auditor (APIP) Case Study In State Attorney Of Grobogan - Endy Dasaatmaja (Jurnal Daulat Hukum, 2019)
The purpose of this study was to determine and analyze the deadline for completion of the calculation of losses to the state by APIPs to requests from law enforcement agencies in Indonesia, especially Attorney Investigator and to determine the actions/policies Attorney Investigator State Prosecutor Grobogan if there are constraints result Counting Losses State Finance APIPs yet immediately handed over to the APH. This study uses a sociological juridical approach with descriptive analytical research specifications. The data used in this study are primary data and secondary data obtained through interviews and literature study, which was then analyzed qualitatively using theories of justice and the theory of legal certainty and legal purposes. The results of this study are: (1) setting a time limit Officials Internal Control of Government (APIP) submit the results of the examination Calculation of state financial loss to the Attorney Investigator regulated under Presidential Decree No. 3 of 2016 on the Acceleration of Project Implementation of the National Strategic, namely that if there is a case report and / or complaints from the public submitted to APH, which was later resolved by the time limit APIPs 35 (thirty-five days) and shall submit from APIPs to the APH later than five (5) days; (2) Measures taken by the State Attorney Investigator Grobogan Related deadline is enhanced to step inquiry investigations, general investigations actions undecided suspects and have not made forceful measures in this regard detention; (3) The ideal concept related settings No time limit need a revision of the Cooperation Agreement which specifically regulates the timeline when APIPs submit the results of the examination results of a calculation of financial loss to the country and incorporate APH 3 of Presidential Decree No. 2016 on Accelerating the implementation of the National Strategic Projects Jo. Presidential Decree No. 58 of 2017 as the legal basis for the deadline of 5 (five) days APIPs into a cooperation agreement between APH with the Internal Ministry. Keywords: Attorney Policy; Corruption; Deadlines; and APIPs.